The impact of political memes on Facebook: A look at two media outlets in Ecuador in 2024 - Echeverría-Escobar, Christian; Parra-Aguirre, Martha (Scripta Mundi, 2025)
In the digital age, social media has transformed the communication, the interaction, and the information consumption. Political memes have become an essential part of online political discourse and a key tool for communication and opinion formation on social media. The objective of this research was to analyze the content, format, and discourse of political memes published on the Facebook pages of two Ecuadorian media outlets during the first quarter of 2024, as well as to evaluate their impact on user perception through the reactions and comments generated. This analysis sought to understand the use of political memes as communication tools in the digital context and their influence on the formation of opinions and attitudes towards political issues in a period marked by significant political events in Ecuador, such as the confrontation between key political figures and debates on violence and national security. A study with a mixed, transversal, and exploratory approach was carried out in which 41 memes published by ‘El suero de la verdad’ and ‘Memes Quito’ were analyzed, pages selected for their relevance in the dissemination of political and humorous content. The results show that 30% of the published memes were political in nature, with satire predominating as the main discourse. The most common reactions were ‘I like it’ and ‘I find it funny’, reflecting positive attitudes, although 27% of the comments showed thematic deviation. The most addressed topics included violence and national politics, reflecting current political events. It is concluded that political memes are effective in capturing attention and amplifying narratives, but their impact on collective action is limited. This study contributes to the understanding of the role of memes in digital political communication in Ecuador, highlighting the need to integrate strategies that enhance their effectiveness in public debate and citizen participation.